Medieval and Early Modern Rituals in Recent Czech and Polish Historiography - Malý, Tomáš (Dějiny – teorie – kritika, 2021)
The study summarises Czech and partially Polish texts on medieval and early modern rituals which have been written in the last three decades. The historiographical preoccupation with rituals and ceremonies is subject to criticism, or it is related to the developments in recent European historiography. We can conclude that both Czech and Polish historians primarily focused on the rituals of the monarchy, which they viewed from the perspective of the main actor, i.e., the king, and considered them a reflection of the political power. Contrary to anthropologists, who are interested in cultural meanings and categories, historians leaned more towards a socio-historical perspective. Descriptions, which partly result in the confirmation of the main actors’ positions of power and partly in an insight into the everyday life and material culture of the power elite, are prominent in the texts. The overall result is a rather reduced reception of anthropological perspective in the analysis of ritual. The current knowledge, essentially dependent on the quality of the existing sources, could be expanded by taking inspiration from spatial studies, e.g., methods developed in recent archaeology, as the conclusion of the study shows.